A Live Attenuated H9N2 Avian Influenza Vaccine Prevents the Viral Reassortment by Exchanging the HA and NS1 Packaging Signals - Chen, Sujuan; Quan, Keji; Wang, Hui; Li, Shi; Xue, Jing; Qin, Tao; Chu, Dianfeng; Fan, Gencheng; Du, Yuanzhao; Peng, Daxin (Frontiers in Microbiology, 2021)
The H9N2 avian influenza virus is not only an important zoonotic pathogen, but also it can easily recombine with other subtypes to generate novel reassortments, such as the H7N9 virus. Although H9N2 live attenuated vaccines can provide good multiple immunities, including humoral, cellular, and mucosal immunity, the risk of reassortment between the vaccine strain and wild type virus is still a concern. Here, we successfully rescued an H9N2 live attenuated strain (rTX-NS1-128 (mut)) that can interdict reassortment, which was developed by exchanging the mutual packaging signals of HA and truncated NS1 genes and confirmed by RT-PCR and sequencing. The dynamic growth results showed that rTX-NS1-128 (mut) replication ability in chick embryos was not significantly affected by our construction strategy than the parent virus rTX strain. Moreover, rTX-NS1-128 (mut) had good genetic stability after 15 generations, possessed low pathogenicity, and no contact transmission characteristics in chickens. Furthermore, chickens were intranasally immunized by rTX-NS1-128 (mut) with a single dose, and the results showed that the hemagglutination inhibition (HI) titers peaked at three weeks after vaccination and lasted at least until 11 weeks. The cellular immunity (IL-6 and IL-12) and mucosal immunity (IgA and IgG) in the nasal and trachea were significantly increased compared to inactivated rTX. Recombinant virus provided a good cross-protection against homologous TX strain (100%) and heterologous F98 strain (80%) challenge. Collectedly, these data indicated that rTX-NS1-128(mut) lost the ability to independent reassortment of HA and NS1-128, and will be expected to be used as a potential live-attenuated vaccine against H9N2 subtype avian influenza.